Integrated Safety Implications for Project Management - Michal Vanek; Yveta Tomaskova; Michal Senovsky; Lucie Krcmarska (Communications - Scientific letters of the University of Zilina, 2013)
Safety insurance provisions in the broadest sense of the term belong among major tasks and challenges for a company management as wellas any municipality administration. In the framework of the decision making process, the manager or administrator takes into account a lot offactors, among which – apart from safety risks – financial possibilities of the company or municipality are of major importance. The decisionsmade have a project character, and managers and administrators can take advantage of project management tools to be able to assess viabilityof the decisions suggested, as well as their implementation. This paper concentrates on the prior-to-investment process of the project management,and the paper’s focal point is in suggesting a method for technical and economic (cost efficiency) assessment of safety projects.